L-Fuzzy Prime Ideals in Universal Algebras - Berhanu Assaye Alaba; Gezahagne Mulat Addis (Advances in Fuzzy Systems)
In this paper, the notions of L-fuzzy prime ideals and maximal L-fuzzy ideals of universal algebras are introduced by applying the general theory of algebraic fuzzy systems.